A STUDY ON THE IMPACT OF BUSINESS ANALYTICS ON DECISION-MAKING BASED ON ONLINE COMMERCE CUSTOMER ORDER DATA - Togtokhbayar, Iderbat; Dari, Chimgee (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
The purpose of this study is to evaluate the impact of business analytics methodologies on the quality of managerial decision-making, based on real online commerce data from Company A for the year 2024. The study utilizes a total of 98,432 order records and includes key variables such as district, sub-district (khoroo), order amount, discounts, promotions, and customer purchase frequency. In Power BI, an interactive dashboard was developed to visualize the organization’s sales performance, discount and promotion policies, regional differences, and seasonal fluctuations. In SPSS, the research hypotheses were tested and validated using correlation, regression, and ANOVA analyses. The results indicate that discount and promotion policies have a statistically significant positive relationship with sales performance.